The role of diet in secondary stroke prevention. Issue 2 (February 2021) - English, Coralie; MacDonald-Wicks, Lesley; Patterson, Amanda; Attia, John; Hankey, Graeme J
Summary: Poor quality diet and nutrition is strongly associated with risk of first stroke, and adherence to a Mediterranean-style diet has been reported to reduce the risk of first stroke. The association between diet quality and the risk of recurrent stroke is less certain and there is no reliable evidence that improving diet quality or dietary supplementation reduces recurrent stroke risk. Current evidence is largely based on epidemiological studies of diverse dietary approaches, ranging from nutritional supplements to specific foods, food groups, and dietary patterns, and is difficult to interpret. In the absence of reliable evidence from randomised clinical trials, the GRADE (Grading of Recommendations Assessment, Development, and Evaluation) approach can be used to assess the potential causal role of diet quality and interventions in reducing recurrent stroke, and to provide guidance for clinical practice and directions for future research. Further work is needed to identify and develop the most promising dietary interventions for evaluation by large randomised clinical trials.